Pengaruh Implementasi Sistem Informasi Manajemen Daerah Terhadap Kualitas Laporan Keuangan pada Satuan Kerja Pemerintah Daerah Kabupaten Nias Selatan - Diana, Patricia; Eforis, Chermian; Osesoga, Maria Stefani (Ultimaccounting Jurnal Ilmu Akuntansi, 2018)
The purpose of this study was to examine the impact of the implementation of Sistem Informasi Manajemen Daerah (SIMDA) toward financial report quality of local government in Nias Selatan. The Indonesian government has encouraged each region to implement Sistem Informasi Manajemen Daerah (SIMDA). SIMDA is an e-government system developed by the Deputi Pengawasan Bidang Penyelenggaraan Keuangan Daerah in order to improve internal control in regional reporting, including local government financial reports. The study was conducted using a survey method to provide the questionnaries to Kepala Sub Bagian Keuangan, Kepala Sub Bagian Program, and Bendahara in 63 Satuan Kerja Perangkat Daerah (SKPD) Nias Selatan. The data used in this study was primary data. There were 154 questionnaries distributed for this research, but only 140 questionnaries returned and used in this research. Data processing using SPSS 24 application with simple regression method. The result of this study was implementation of Sistem Informasi Manajemen Daerah (SIMDA) has significant impact toward financial report quality of local government in Nias Selatan. Keywords : financial report quality, local government financial statements, SIMDA